Matrix used in Input and Output Analysis - Zhang, Litao (Transactions on Economics, Business and Management Research, 2024)
This report focuses on Mathematics associated with Economics. It states that the matrix is used in the input-output Analysis in the economic field using Wassily Leontief’s Theory. This report comprises six main parts dedicated to comprehensively explaining the origin of Wassily Leontief’s theory, its application, and its limitations and improvements. The second part of this paper briefly introduces matrices, such as definition and simple or complicated matrix Algebra. The third part of this passage describes the introduction of the input and output system and its combination with mathematical calculation to derive the demand curve. The fourth part focuses on the background of Professor Wassily Leontief, the derivation of Wassily Leontief’s Theory, and the arithmetic of his theory by illustrating two numerical examples. The fifth part discusses real-world applications, points out a general implementation framework based on the thesis, and makes a more summarizing statement. The sixth part considers some typical limitations of real-world applications of Wassily Leontief’s input-output Analysis and provides some handle solutions.